The Role of Strategic Leadership in Strengthening Human Resource Resilience in Madrasah Diniyah - Unzilah Khomairohtusshiyamah; Rifka Jannatul Firdausiyah; Hefni Razaq (APPLICATION: Applied science in Learning Research, 2026)
This research aims to understand how strategic leadership plays a role in strengthening the resilience of human resources (HR) in Madrasah Diniyah. This study departs from the phenomenon of the gap between the ideal concept of strategic leadership and practice in Islamic educational institutions. Many institutions still tend to focus on administrative aspects, so they are not optimal in building resilient and adaptive human resources. This condition is also influenced by the limitations of leadership competence, the lack of integration between spiritual values and modern management, and the weak organizational culture. On the other hand, Madrasah Diniyah actually shows a different condition, where educators still have high commitment, are active in developing themselves, are able to adapt, and maintain collaboration despite facing various limitations and demands for change. This research uses a qualitative approach with a case study type. Data is collected through observation, in-depth interviews, and documentation, then analyzed through a process of reduction, presentation, and conclusion drawn. The results of the study show that strategic leadership plays an important role in building human resource resilience through clarity of vision, consistent communication, and the inculcation of institutional values. In addition, leaders also encourage capacity development, adaptability, and a collaborative work culture. The implications of this study confirm that strengthening human resource resilience is not enough only through a managerial approach, but needs to be combined with spiritual values and organizational culture so that the sustainability and quality of educational institutions can be maintained in a sustainable manner